ANALISIS SEGMENTASI, TARGETING DAN POSITIONING STUDI KASUS KERIPIK KENTANG LEO - Anaseputri Jamira (Universitas Batanghari Jambi, 2017)
The purpose of this study is to find out Segmenting, Targeting, and Positioning (STP) of Leo Potato Crisps Snack from Garudafood. To analyze segmenting, targeting, and positioning of Leo, descriptive method reflecting the execution of STP is used. The data used include primary and secondary data. The data obtained is then analyzed by qualitative analysis and then compared with related theories. The results show that Leo brand chose market specialization that the target market is teenagers, junior high school students, ranging from age 13-15 years. Leo brand is positioned as a potato crisps product with relatively cheaper price and more content volume (Attribute Positioning). This is in accordance with the tag line that is always communicated is